2022
DOI: 10.3390/biomedicines10102480
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy (SBRT) of Pancreatic Cancer—A Critical Review and Practical Consideration

Abstract: Pancreatic cancer is the third leading cause of cancer death in the developed world and is predicted to become the second by 2030. A cure may be achieved only with surgical resection of an early diagnosed disease. Surgery for more advanced disease is challenging and can be contraindicated for many reasons. Neoadjuvant therapy may improve the probability of achieving R0 resection. It consists of systemic treatment followed by radiation therapy applied concurrently or sequentially with cytostatics. A novel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…However, the previously discussed Alliance trial A021501 did not definitively support the use of neoadjuvant radiation [ 12 ]. This is still an area of exploration, especially as newer techniques for radiation delivery become refined [ 31 , 32 ]. In addition to medical therapy, the advancement of the understanding of the role of neoadjuvant radiation therapy may result in a truly multidisciplinary approach to the management of surgically resectable pancreatic cancer.…”
Section: Future Outlooksmentioning
confidence: 99%
“…However, the previously discussed Alliance trial A021501 did not definitively support the use of neoadjuvant radiation [ 12 ]. This is still an area of exploration, especially as newer techniques for radiation delivery become refined [ 31 , 32 ]. In addition to medical therapy, the advancement of the understanding of the role of neoadjuvant radiation therapy may result in a truly multidisciplinary approach to the management of surgically resectable pancreatic cancer.…”
Section: Future Outlooksmentioning
confidence: 99%
“…In addition, more precise radiation therapy can reduce the incidence of radiation damage. For example, stereotactic body radiation therapy (SBRT) is a relatively novel approach to irradiation that delivers higher doses of radiation to the tumor in only a few treatment fractions [ 147 ] and has been used to treat a variety of cancers. In the treatment of pancreatic cancer, SBRT can safely facilitate marginal negative resection in borderline resectable pancreatic cancer (BRPC) while avoiding damage to normal tissues [ 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pancreatic cancer have a low survival rate and are prone to local recurrence. SBRT combined treatment modalities have been recommended by guidelines published by the Australasian Gastrointestinal Trials Group (AGITG) and the Trans-Tasman Radiation Oncology Group (TROG) 3 . Lischalk et al showed that delivering 25-30 Gy over 5 fractions of segmented SBRT can significantly improve local PTV control in pancreatic cancer patients with minimal radiation toxicity 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It can achieve single high-dose irradiation of tumors, increasing the lethality of tumor cells. International consensus guidelines recommend SBRT as a new treatment modality for pancreatic cancer 3 .…”
Section: Introductionmentioning
confidence: 99%